Evaluation of a manual identification system for detection of Mycobacterium tuberculosis in a primary tuberculosis laboratory in China. Issue 6 (June 2019) - Zhao, Ping; Yu, Qin; Zhang, Yu
Objective: To compare the diagnostic performance of the manual BACTEC™ Mycobacteria Growth Indicator Tube (MGIT™) system (M-MGIT) with the automated BACTEC™ MGIT™ 960 system (A-MGIT) and Löwenstein-Jensen (L-J) culture method in detecting mycobacteria in sputum specimens from patients with suspected pulmonary tuberculosis (TB). Methods: For this cross-sectional study, sputum samples were taken from patients aged ≥18 years attending a TB clinic in Beijing, China between July 2015 and October 2016. Processed sputum samples were inoculated into the MGIT systems and L-J medium for up to 6 and 8 weeks, respectively. Results: The M-MGIT and A-MGIT methods detected significantly more Mycobacterium tuberculosis complex (MTC) isolates than L-J culture from the 565 sputum samples (39%, 40% and 32%, respectively). Using a positive result from any of the three culture systems as reference, the sensitivity of M-MGIT, A-MGIT and L-J methods were 92%, 94%, and 74%, respectively. The time-to-detection of mycobacteria was 12.9±4.2 days for M-MGIT, 11.8±5.2 days for A-MGIT and 24.2±8.7 days for L-J. Conclusions: M-MGIT has a similar diagnostic performance to A-MGIT, and is a fast and reliable alternative to conventional culture methods in the diagnosis of pulmonary TB in a developing country.